Assessing the potential of translocating vulnerable forest birds by searching for novel and enduring climatic ranges. Issue 21 (27th September 2017) - Fortini, Lucas B.; Kaiser, Lauren R.; Vorsino, Adam E.; Paxton, Eben H.; Jacobi, James D.
Abstract: Hawaiian forest birds are imperiled, with fewer than half the original >40 species remaining extant. Recent studies document ongoing rapid population decline and project complete climate‐based range losses for the critically endangered Kaua'i endemics 'akeke'e ( Loxops caeruleirostris ) and 'akikiki ( Oreomystis bairdi ) by end‐of‐century due to projected warming. Climate change facilitates the upward expansion of avian malaria into native high elevation forests where disease was historically absent. While intensified conservation efforts attempt to safeguard these species and their habitats, the magnitude of potential loss and the urgency of this situation require all conservation options to be seriously considered. One option for Kaua'i endemics is translocation to islands with higher elevation habitats. We explored the feasibility of interisland translocation by projecting baseline and future climate‐based ranges of 'akeke'e and 'akikiki across the Hawaiian archipelago. For islands where compatible climates for these species were projected to endure through end‐of‐century, an additional climatic niche overlap analysis compares the spatial overlap between Kaua'i endemics and current native species on prospective destination islands. Suitable climate‐based ranges exist on Maui and Hawai'i for these Kaua'i endemics that offer climatically distinct areas compared to niche distributions of destination island endemics. While we recognize that any decision to translocate birds will include assessing numerous additional social, political, and biological factors, our focus on locations of enduring and ecologically compatible climate‐based ranges represents the first step to evaluate this potential conservation option. Our approach considering baseline and future distributions of species with climatic niche overlap metrics to identify undesirable range overlap provides a method that can be utilized for other climate‐vulnerable species with disjointed compatible environments beyond their native range. Abstract : The steep ongoing and projected declines for Kaua'i forest birds indicate all conservation options must be seriously considered. We explored the feasibility of interisland translocation for the critically endangered Kaua'i endemics 'akeke'e (Loxops caeruleirostris) and 'akikiki (Oreomystis bairdi) across the Hawaiian archipelago. To do that, we identified areas outside of Kaua'i that are likely to remain climatically suitable for these species under multiple future climate scenarios and offer the least climatic niche overlap with native species already present.